Analysis Of The Effect Of Price, Quality, Promotion, And Brand Image Of Skintific On Students Buying Interest - Marhayani, Ilsa; Handayani, Sri; Efendi, Yanto (BIMA Journal (Business, Management, & Accounting Journal), 2025)
ABSTRACT Purpose: This study aims to analyze the effect of price, promotion quality, and Skintific brand image on students’ purchase intention toward Skintific skincare products. Methodology: This research adopts a quantitative approach using a descriptive survey method. Data were collected through structured questionnaires distributed to 100 student respondents who use Skintific products. The data were analyzed using validity and reliability tests, multiple linear regression analysis, t-tests, f-tests, and the coefficient of determination (R²). Results: The results indicate that price, promotion quality, and Skintific brand image have a positive and significant effect on students’ purchase intention, both partially and simultaneously. The coefficient of determination (R²) of 0.803 shows that 80% of the variation in purchase intention is explained by the examined variables, while the remaining 20% is influenced by other factors not examined in this study. Novelty: This study provides an integrated empirical model examining price, promotion quality, and brand image in the context of skincare consumption among students. Findings: Brand image and promotion quality emerge as key drivers of students’ purchase intention, supported by competitive pricing. Originality: The originality of this study lies in its focus on student consumers and the Skintific skincare brand within the Indonesian market. Conclusions: Strengthening brand image, improving promotional quality, and maintaining competitive pricing can significantly enhance students’ purchase intention. Type of Paper: Empirical Research Paper.